Bulgaria Spending Review on Policing and Firefighting - World Bank Group (World Bank, Washington, DC, 2018)
In 2016, the Government of Bulgaria (GoB) decided to initiate spending reviews to improve the efficiency and effectiveness of its spending in the context of a moderate fiscal consolidation process. Though Bulgaria has one of the lowest overall spending in the European Union (EU), spending outcomes lag those of other EU member states. In the case of public order and safety, Bulgaria spends the most among comparable EU countries but outcomes are not satisfactory. Surveys show that citizens have low confidence on the effectiveness of police. Police and firefighters in turn, have said that their effectiveness is constrained by the condition of equipment, excessive time spent on paperwork, additional responsibilities imposed in the frequently changed legislation, and by curtailed staff benefits. To help address these challenges the Ministry of Finance (MoF) requested analytical and advisory support from the World Bank. Such support was intended to identify spending pressures and potential efficiency and effectiveness gains in policing and firefighting. In contrast to most spending reviews, where saving targets are identified upfront and the primary objective is to find ways of reducing the budget, the primary objective of this review is to increase performance and use any savings derived from efficiency gains for additional priority spending on policing and firefighting.